Розробка компонентів інформаційної системи «онлайн-платформа інтерактивних вікторин» - Котенко, І. І. (ХНУРЕ, 2024)
This work is devoted to the development of an interactive quiz platform. Both the server and client parts of the system have been developed to create and pass quizzes. The main supported quiz type is the “Tournament” where participants choose their preferred option from a pool on a specific topic. Other more common quiz types were considered. With the help of this platform, you can perform various actions on quizzes, such as passing them, viewing individual and general results of passing, rating by clicking “Like” or “Dislike”, adding to wanted list to not lose and pass later, create your own quizzes.
Keywords: interactive quiz platform; онлайн-платформа; інтерактивні вікторини